‘Control is up to me’: youth narratives on the problematic use of ICTs - Palacios Ramírez, José; Rodes García, Joaquín; Nogués Pedregal, Antonio M. (Frontiers in Human Dynamics, 2025)
IntroductionScientists and social planners have stressed that the use of ICTs by young people may result in risky and addictive behaviours. Research on this topic tends to correlate psychological variables and time use metrics from a clinical perspective. This paper suggests a sociocultural approach to deepen the understanding of the problematic ICT use, as perceived by young people.MethodsCombination of questionnaires and in-depth interviews with young people living in a Spanish city was used to study the point of view of youth.ResultsResults point to the problematic use of ICTs as part of youth culture in a digitalised society. Informants are consciously aware of negative effects of ICTs on their own day to day life. It is observed that their narratives are structured by an addiction terminology, while society is depicted as digitalised and the use of ICTs as innate among younger generations.DiscussionMoreover, this study suggests that young people are more inclined towards self-management of digital risks, as the narratives collected focus mostly on individual responsibility and self-learning. These findings help to expand empirical evidence on individuals’ management of digital risk while calling into question stereotyped views of youth, either as digital natives or addicts. The conclusion is that a community-based approach is needed to address problematic ICT use.